(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Attention Deficit Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder during child development with three symptoms which are comprised of inattention, hyperactivity, and impulsiveness that may persist into adulthood. This condition can be a stressor for parents in performing parenting and may lead into a state of parenting stress. Objective: To analyze the relationship between parenting stress and the risk of developing Attention Deficit Hyperactivity Disorder (ADHD) in elementary school children. Methods: This research was conducted in Surabaya from November 2020 to January 2021 with respondents consisting of parents of elementary school children who have ADHD risk and agreed to participate in this study with a total of 55 samples selected using a purposive sampling technique. The research design was cross-sectional using demographic questionnaire, Abbreviated Conners Rating Scale (ACRS), and Parenting Stress Index-Short Form (PSI-SF) which were filled out by respondents through an online form. The data were processed and analyzed using One-Sample Chi-Square analysis test program with a p-value <0.05, considered statistically significant. Results: The majority of parents experienced moderate parenting stress levels (58.2%). There was a significant relationship between each level of parenting stress and the risk of ADHD in children (p < 0.001). Conclusions: There is a significant relationship between parenting stress and the risk of ADHD in children.